The Understanding of Body and Soul in Matthew 10:28 espoused by Seventh-day Adventist Church - Masilon, Adee Lindon (Fakultas Filsafat Universitas Advent Indonesia, 2023)
The body/soul contrast has been a hot topic of discussion. Matthew 10:28 is one of those biblical text that talks about body and soul, though not in an extensive manner. From the text, it seemed like Jesus understood that body and soul can be destroyed separately. Does this mean that body and soul are two separate and independent entities? The Seventh-day Adventists believe that there is no immortal and separate entity, called soul, living within the physical human body. It is more fitting to say that a human being is a living soul rather than to say that he has a soul. The purpose of this study is to bring harmony between Jesus’ saying in Matthew 10:28 with the teachings of the Seventh-day Adventists regarding body and soul. A review on the word “body” and “soul” and also a review on the context were conducted to solve the problem of this study. In truth, Matthew chapter 10 is not a discourse on body and soul but rather a record of Jesus’ mission charge to the twelve disciples. Thus, verse 28 should be evaluated from the lenses of mission. The study has shown that the audience of Jesus could be the ones who possess that wrong concept of body and soul, whereas Jesus did not contradict the Seventh-day Adventist belief that states the soul is not an immortal, separate entity living within the body. The result of the study has shown that the Seventh-day Adventist’s belief regarding body and soul is valid. In this particular text, Jesus is using a common concept to point to the truth that God is more powerful than human oppositions.